Proposed methods for reviewing the outcomes of health research: the impact of funding by the UK's 'Arthritis Research Campaign' - Wooding Steven; Grant Jonathan; Hanney Stephen R; Buxton Martin J (BMC, 2004)
Abstract Background External and internal factors are increasingly encouraging research funding bodies to demonstrate the outcomes of their research. Traditional methods of assessing research are still important, but can be merged into broader multi-dimensional categorisations of research benefits. The onus has hitherto been on public sector funding bodies, but in the UK the role of medical charities in funding research is particularly important and the Arthritis Research Campaign, the leading medical charity in its field in the UK, commissioned a study to identify the outcomes from research that it funds. This article describes the methods to be used. Methods A case study approach will enable narratives to be told, illuminating how research funded in the early 1990s was (or was not) translated into practice. Each study will be organised using a common structure, which, with careful selection of cases, should enable cross-case analysis to illustrate the strengths of different modes and categories of research. Three main interdependent methods will be used: documentary and literature review; semi-structured interviews; and bibliometric analysis. The evaluative framework for organising the studies was previously used for assessing the benefits from health services research. Here, it has been specifically amended for a medical charity that funds a wide range of research and is concerned to develop the careers of researchers. It was further refined in three pilot studies. The framework has two main elements. First, a multi-dimensional categorisation of benefits going from the knowledge produced in peer reviewed journal articles through to the health and potential economic gain. The second element is a logic model, which, with various stages, should provide a way of organising the studies. The stock of knowledge is important: much research, especially basic, will feed into it and influence further research rather than directly lead to health gains. The cross-case analysis will look for factors associated with outcomes. Conclusions The pilots confirmed the applicability of the methods for a full study which should assist the Arthritis Research Campaign to demonstrate the outcomes from its funding, and provide it with evidence to inform its own policies.